Not with a Ten-Foot Pole: Core Stigma, Stigma Transfer, and Improbable Persistence of Men's Bathhouses - Hudson, Bryant Ashley; Okhuysen, Gerardo A. (Organization Science, 2009)
We examine how organizations that suffer core stigma—disapproval for their core attributes—survive. We explain how men's bathhouses avoid negative attention and minimize the transfer of stigma to their network partners, including customers, suppliers, and regulators, through careful management of their business activities. Using observational, archival, and interview data across different institutional environments, we find that, in response to suffering core stigma, men's bathhouses use a variety of strategies to shield their partners depending, in part, on the level of hostility that they face in their environment. Our work contributes to the emerging literature on organization-level stigma, especially by focusing on how core-stigmatized organizations are able to survive and by drawing attention to the special problem of stigma transfer. Our findings also focus attention on the use of legitimacy in organization studies and call for further examinations of core-stigmatized and other illegitimate organizations to expand our theoretical domain to the fullest range of organizational processes and outcomes.